Entwicklung prozessüberwachender Regelkreise für flexible Formgebungsprozesse - Hutterer, Angelika (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2005)
Flexible forming processes like laser forming are using independent tools and are thus suitable for fast and efficient product development. High accuracy and reproducibility of the products is the precondition of the production. This thesis describes methods and algorithms tor a feature based closed loop control system. The closed loop control system is realized exemplarily for the laser forming of extrusions and the laser adjustment of free form surfaces. The systems could be applied in the field of space frame technology or in the adjustment of warpage in the car body industr